Możliwości zwalczania zwójek jodłowych Choristoneura murinana Hb., Zeiraphera rufimitrana H.-S. i Epinotia nigricana H.-S. w lasach Gór Świętokrzyskich - Głowacka, Barbara; Bystrowski, Cezary (Leśne Prace Badawcze, 2012)
Fir shoot moths Choristoneura murinana Hb., Zeiraphera rufimitrana H.-S. and Epinotia nigricana H.-S. occur every few decades in the outbreaks in Świętokrzyskie Mountains’ stands, causing substantial damage to the fir trees. Then fir trees are attacked and killed by cambio- and xylophagous insects. During the last outbreak two trials with the use of aircraft were carried out to control fir shoot moths at the Łagów Forest Distrit. In 2008 insecticides were used in doses and volumes of spray solutions registered for a control of pine foliophagous insects: Dimilin 480 SC and Mospilan 20 SP were applied at the doses of 0,2 l and 0,2 kg/ha, both in 5 1/ha of spray solution. In 2010 doses and volumes of spray solutions were increased: Dimilin 480 SC was used at the dose of 0.3 l / ha and Mospilan 20 SP was used at the dose of 0.4 kg/ha, both were applied in 10 l/ha of spray solution. The efficacy was assessed 3–4 weeks after spraying by cutting down sprayed and untreated (control) trees on 4×5 m linen cloth sheets. Alive and dead caterpillars and pupae of shoot moths found in the crowns were collected and counted. With the use of Abbott’s formula their mortality was calculated. In 2008 mortality rates ranged from 5,7% to 15,4% in stands where Dimilin 480 SC was used and from 2,8% to 8,6% in stands sprayed with Mospilan. In 2010 Dimilin caused death of 75,4–80,1% and Mospilan 86,6–89,5% of fir shoot moth larvae The low pest mortality in 2008 was probably a result of too low dose of insecticides and insufficient coverage of fir needles with spray droplets resulting from the large size of tree crowns. Results obtained in 2010 demonstrate higher efficacy of Mospilan 20 SP and they will be the basis for registration of the insecticide to protect fir stands against shoot moth.